Optimal Point-Wise Error Estimate of Two Second-Order Accurate Finite Difference Schemes for the Heat Equation with Concentrated Capacity (Journal of Computational Mathematics, 2026)
In this paper, we propose and analyze two second-order accurate finite difference schemes for the one-dimensional heat equation with concentrated capacity on a computational domain $Ω = [a, b].$ We first transform the target equation into the standard heat equation on the domain excluding the singular point equipped with an inner interface matching (IIM) condition on the singular point $x = ξ ∈ (a, b),$ then adopt Taylor’s expansion to approximate the IIM condition at the singular point and apply second-order finite difference method to approximate the standard heat equation at the nonsingular points. This discrete procedure allows us to choose different grid sizes to partition the two sub-domains $[a, ξ]$ and $[ξ, b],$ which ensures that $x = ξ$ is a grid point, and hence the proposed schemes can be generalized to the heat equation with more than one concentrated capacities. We prove that the two proposed schemes are uniquely solvable. And through in-depth analysis of the local truncation errors, we rigorously prove that the two schemes are second-order accurate both in temporal and spatial directions in the maximum norm without any constraint on the grid ratio. Numerical experiments are carried out to verify our theoretical conclusions.
Keywords: Heat equation with concentrated capacity; Finite difference scheme; Inner interface matching condition; Unconditional convergence; Optimal error estimate